Ibn Fadlan and the land of darkness Arab travellers in the far north - Ibn Faḍlān, Aḥmad (Penguin classics, 2012)
Between the ninth and fourteenth centuries, Arab travellers such as Ibn Fadlan journeyed widely and frequently into the far north, crossing territories that now include Russia, Uzbekistan and Kazakhstan. This title offers an illuminating insight into the world of the Arab geographers, and the medieval lands of the far north